Socialização da informação: intersecções temáticas entre ciência da informação e educação - Silva, Márcio Felipe Albuquerque Prazim da (2014)
Analyzes the field interface between Information Science (SI) and Education relating the information socialization to the Paulo Freire scontributions, mainly from procedures specified in Pedagogy of the Oppressed, which can guide the formation of communicative context. At the end, encourages conceptual map is based on the discussion of information socialization. This is theoretical research in interthematic part, and also focuses on interdisciplinary relationships between fields of knowledge. Regarding the objectives, initiallyis defined as exploratory research and, after, as a descriptive, qualitative approach. SI believes that education and built a fruitful interface, which motivates a deeper reflection on the contributions that emerged at the heart of this dialogic space of contemporary society, in the study, understood as learningsociety or learning network society. The information socialization comprises studies of SI and can relate to the field of Education through Paulo Freire s theoretical and procedural guidance, since the formation of the communicative context to creating informational products.